Importância da intoxicação espontânea por Niedenzuella stannea (Malpighiaceae) em bovinos no estado de Mato Grosso e reprodução do quadro clínico e lesional da intoxicação em ovinos - Caldeira, Flávio Henrique Bravim (2016)
The aim of this study was to investigate the importance of an acute disease that is characterized by sudden death associated with exercise, which affects cattle in the region of the Araguaia River, especially in the municipality of Torixoréu, in the southeastern region of the State of Mato Grosso, Brazil, and also report the clinical and pathological findings of experimental poisoning by Niedenzuella stannea in sheep. Between August and September 2013, 80 farms in the municipality were visited, and the pastures of these farms were inspected. Epidemiological questionnaires were completed in 65 farms. A plant identified as Niedenzuella stannea (Malpighiaceae) was attributed to the cause of sudden death in cattle causing major economic losses. Sudden death reports have occurred since 1970 when livestock was introduced in the region, and sudden death reports still occur to date. Outbreaks were reported to occur in different months of the year, ranging from May to October, mainly during the dry season between June and August. N. stannea was identified at 41 properties, and it was always found close to rivers. The most effective plant control methods included plowing the pastures and fields followed by manual application of Tordon® (Picloran and 2.4D). N. stannea was collected in areas with history of sudden death in cattle. We evaluated two growing stages of the plant: mature, which were fibrous and dark green color and young leaves which had tender and bright green. Leaves of N. stannea were administered to eleven sheep. Adult leaves caused no clinical changes in doses of 5-40g/kg. Clinical and pathological changes were only observed in the group of animals who received shoots of N. stannea. Clinical signs observed in sheep received a single dose of 30g/kg were anorexia, lethargy, dyspnea, tachycardia arrhythmia and clinical course varying from 16 to 20h. Was noted a hyperacute terminal phase characterized by reluctance to move, frequent urination engorged jugular, obvious venous pulse, muscle tremor, sternal recumbency and lateral recumbency and death in clinical evolution average of 10 minutes. At necropsy the main findings were engorgement of the large veins and atrium of the heart and pulmonary edema. Microscopically observed degeneration with nuclear picnosis in the epithelium of distal convoluted tubules. Sodium monofluoroacetate was characterized as a principle of N. stannea related to the clinical picture. In this study, the signs of intoxication were precipitated by the movement in all sheep, which is also reported in cases of spontaneous poisoning mainly in the managements for obligatory vaccinations. This factor puts N. stannea the group of plants that cause sudden death and should therefore be considered in the differential diagnosis of clinical cases of acute evolution in the central regions of Brazil. It was concluded that the sudden deaths in cattle in areas of the basin of the Araguaia river are due to the consumption of N. stannea.